2017
DOI: 10.1002/ajmg.a.38069
|View full text |Cite
|
Sign up to set email alerts
|

A de novo splice site mutation in CASK causes FG syndrome‐4 and congenital nystagmus

Abstract: Mutations in CASK cause X-linked intellectual disability, microcephaly with pontine and cerebellar hypoplasia, optic atrophy, nystagmus, feeding difficulties, GI hypomotility, and seizures. Here we present a patient with a de novo carboxyl-terminus splice site mutation in CASK (c.2521-2A>G) and clinical features of the rare FG syndrome-4 (FGS4). We provide further characterization of genotype-phenotype correlations in CASK mutations and the presentation of nystagmus and the FGS4 phenotype. There is considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The proteins included in MAGUK family are scaffold proteins and are located at synapses in the brain. Various neurological disorders have been associated with CASK; FG syndrome (5,6), X-linked ID with/without nystagmus (7), and epileptic encephalopathy (8)(9)(10). In this study, a novel CASK mutation, c.1424G>T (p.Ser475Ile), was identified in siblings exhibiting DD with ID and/or ASD.…”
Section: Introductionmentioning
confidence: 80%
“…The proteins included in MAGUK family are scaffold proteins and are located at synapses in the brain. Various neurological disorders have been associated with CASK; FG syndrome (5,6), X-linked ID with/without nystagmus (7), and epileptic encephalopathy (8)(9)(10). In this study, a novel CASK mutation, c.1424G>T (p.Ser475Ile), was identified in siblings exhibiting DD with ID and/or ASD.…”
Section: Introductionmentioning
confidence: 80%
“…The affected female from our cohort did not present such a severe phenotype. Considering her young age though, her clinical course might deteriorate, although a wide variability in clinical phenotype has been observed even among cases with variants predicted to have similar effects on protein functionality (Dunn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, three girls showed ophthalmologic anomalies and two of them specifically displayed nystagmus. Previous reports have indicated that congenital nystagmus is strongly associated with mutations localized in the GUK domain of CASK (Dunn et al, 2017; Hackett et al, 2010; Watkins et al, 2013). This domain interacts with FRMD7, a plasma membrane-cytoskeleton coupling protein, mutations of which cause X-linked congenital nystagmus (Tarpey et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In children, vertical nystagmus may be linked to retinal dystrophies [62]. Different nystagmus patterns may be seen in newborn and infants with Joubert syndrome [63], mutations in the calcium/ calmodulin-dependent serine protein kinase (CASK) gene leading to FG-syndrome 4 [64], visual deprivation from child neglect [65], mass lesions above the midbrain [66] and galactokinase deficiency [67]. The differential diagnosis of isolated nystagmus in pediatric patients remains challenging.…”
Section: Nystagmus In the Differential Diagnosismentioning
confidence: 99%